Closing Rural-Urban MDG Gaps in Low-Income Countries : A General Equilibrium Perspective - Lofgren, Hans (World Bank, Washington, DC, 2013)
This paper addresses policies aimed at closing the rural-urban gap for one of the Millennium Development Goals (MDGs), the under-five mortality rate (U5MR). The paper relies on the Maquette for MDG Simulations (MAMS), a computable general equilibrium model, applied to the database of an archetypical low-income country. The scenarios, which focus on the period 2013-2030, include a "business-as-usual" base scenario and policy scenarios that analyze efforts to raise the rural population up to the urban level in terms of health services or the under-five mortality rate. The policy scenarios are implemented with alternative sources of fiscal space. The results indicate that, if current trends continue, considerable progress for MDGs should be expected by 2030. If the government raises rural health services, then the decline in the rural U5MR would accelerate. If most additional resources come from foreign grants or government efficiency gains, then the repercussions for other development indicators, including poverty reduction, would be positive. However, if most additional resources are from domestic taxes or borrowing, then progress for the rural U5MR would come at the expense of less progress for other indicators. Sensitivity analysis shows that these qualitative findings are robust to different values for two parameters related to initial rural-urban cost and service gaps. However, quantitatively, the results depend on the values of these two parameters, implying that individual country characteristics strongly influence the fiscal-space requirements for and consequences of equalizing rural-urban MDG services and outcomes.